4(x-3)+2(x-1)=

Simple and best practice solution for 4(x-3)+2(x-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-3)+2(x-1)= equation:


Simplifying
4(x + -3) + 2(x + -1) = 0

Reorder the terms:
4(-3 + x) + 2(x + -1) = 0
(-3 * 4 + x * 4) + 2(x + -1) = 0
(-12 + 4x) + 2(x + -1) = 0

Reorder the terms:
-12 + 4x + 2(-1 + x) = 0
-12 + 4x + (-1 * 2 + x * 2) = 0
-12 + 4x + (-2 + 2x) = 0

Reorder the terms:
-12 + -2 + 4x + 2x = 0

Combine like terms: -12 + -2 = -14
-14 + 4x + 2x = 0

Combine like terms: 4x + 2x = 6x
-14 + 6x = 0

Solving
-14 + 6x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + 6x = 0 + 14

Combine like terms: -14 + 14 = 0
0 + 6x = 0 + 14
6x = 0 + 14

Combine like terms: 0 + 14 = 14
6x = 14

Divide each side by '6'.
x = 2.333333333

Simplifying
x = 2.333333333

See similar equations:

| -10(a+3)+6a= | | 7c-15-5c+42= | | 12-2c=2whatisc | | 6(n+3)+2n= | | -7(y-11)= | | -5+6c-5c= | | 5(1+3x)=125 | | -3n+8+8n= | | 40h+25k+35= | | -8c+c= | | -3a+11a= | | 305=0.15x+16y | | 9=2y-(2y-9) | | 2(x+15)=16 | | 305=0.15y+16x | | (7x+3y)-(2x-3y)= | | 10m-8m= | | -12-15x=3 | | 6(6+3x)=54 | | 24x+24y= | | -4(r-4s-9t)= | | 19.6t^2-14t+8=0 | | 45(-11-32)=c | | x-5=2(23.5)+12 | | -8(2t+6)=-112 | | 16=y+2 | | 2(4x-2)=7x | | 8(s-10)=-124 | | 16a^2-24a+1=0 | | -4+2x=-8+16 | | 4(10+7x)=152 | | 2secx+8sinx=0 |

Equations solver categories